Legal Provisions On Breach Of Contract In The Execution Of House Lease-Pawn Agreements In The Perspective Of Article 1238 Of The Indonesian Civil Code - Raihan Irsyad, Radja; Alfiany, Temmy Fitriah; Mulyanti, Asti Sri (Dinasti Research, 2025)
The practice of house lease-pawn agreements in rural communities is frequently employed as an alternative means of meeting economic needs, often without adherence to formal legal provisions. This study aims to analyze the legal framework governing house lease-pawn agreements under Article 1338 of the Indonesian Civil Code, which embodies the principle of freedom of contract, as well as to examine the legal implications of breach of contract in such agreements pursuant to Article 1238 of the Civil Code. Employing a normative juridical approach, this research incorporates a case study conducted in Kampung Cijambe, Sukabumi City. The findings indicate that house lease-pawn agreements constitute innominate contracts, which are legally valid provided they satisfy the requirements stipulated in Article 1320 of the Civil Code. In instances of breach of contract, the aggrieved party is entitled to seek contract annulment, compensation, and legal recourse through judicial mechanisms. The study underscores the necessity of drafting written agreements that ensure legal certainty and advocates for regulatory reinforcement regarding the practice of house lease-pawn agreements.